2023
DOI: 10.1108/jeas-12-2022-0260
|View full text |Cite
|
Sign up to set email alerts
|

Risk management implementation and its efficacy towards green innovation: a conceptual framework for Malaysian solar photovoltaic industry

Abstract: PurposeThis study aims to propose a conceptual framework to examine the impact of risk management implementation on green innovation in the Malaysian solar photovoltaic (PV) manufacturing industry.Design/methodology/approachThe study is based on primary data to be collected from 30 Malaysian solar PV manufacturing companies through a questionnaire that incorporates the five-point Likert scale. The exploratory factor analysis (EFA) is proposed to be performed using SPSS 24.0 and confirmatory factor analysis (CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Furthermore, Yusr et al (2020) concluded that green innovative enterprises, even those who practice green in their products and processes, can achieve high levels of sustainable economy by reducing waste and enhancing productivity. Thus, overall, enterprises with higher green innovation achieve greater energy efficiency and curb environmental issues that strengthen their eco-friendly image, ultimately contributing to higher profitability (Mukhtar et al , 2023b). Thus, overall, enterprises with higher green innovation achieve superior energy efficiency and curtail environmental issues that boost their eco-friendly image, ultimately contributing to higher profitability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, Yusr et al (2020) concluded that green innovative enterprises, even those who practice green in their products and processes, can achieve high levels of sustainable economy by reducing waste and enhancing productivity. Thus, overall, enterprises with higher green innovation achieve greater energy efficiency and curb environmental issues that strengthen their eco-friendly image, ultimately contributing to higher profitability (Mukhtar et al , 2023b). Thus, overall, enterprises with higher green innovation achieve superior energy efficiency and curtail environmental issues that boost their eco-friendly image, ultimately contributing to higher profitability.…”
Section: Literature Reviewmentioning
confidence: 99%